2017
DOI: 10.1186/s13613-016-0230-9
|View full text |Cite
|
Sign up to set email alerts
|

Invasive fungal tracheobronchitis in mechanically ventilated critically ill patients: underlying conditions, diagnosis, and outcomes

Abstract: BackgroundInvasive fungal tracheobronchitis (IFT) is a severe form of pulmonary fungal infection that is not limited to immunocompromised patients. Although respiratory failure is a crucial predictor of death, information regarding IFT in critically ill patients is limited.MethodsIn this retrospective, multicenter, observational study, we enrolled adults diagnosed as having IFT who had been admitted to the intensive care unit between January 2007 and December 2015. Their demographics, clinical imaging data, br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 38 publications
1
22
0
2
Order By: Relevance
“…In recent decades, we found that not only immunocompromised patients were susceptible to fungal infections, diabetes mellitus, chronic lung diseases may also experience invasive fungal infections [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, we found that not only immunocompromised patients were susceptible to fungal infections, diabetes mellitus, chronic lung diseases may also experience invasive fungal infections [4].…”
Section: Discussionmentioning
confidence: 99%
“…This study included 47 IPA ( 34 proven IPA and 13 probable IPA) and 22 PM patients (21 with proven PM and one with probable PM, Figure 1). Among these patients, 19 IPA patients and eight PM patients were reported in our published article [4]. There were four patients having concomitant IPA and PM, of which three were categorized as PM and one as IPA by histopathology.…”
Section: Patients' Characteristicsmentioning
confidence: 95%
“…In that study, the success rate in the isavuconazole group was 60.3% vs. 71.1% in the caspofungin group [81]. A pooled analysis was performed of patient-level data from seven randomized antifungal treatment trials, using 30-day mortality as the primary endpoint [55].…”
Section: What Are Remaining Areas Of Uncertainty? Invasive Candidiasismentioning
confidence: 99%
“…[80] identified during the last decade including COPD, liver failure, cirrhosis, and post-H1N1 influenza [27,28]. The diversity of patients and risk factors complicates diagnostic and therapeutic procedures while the available data in critically ill patients are extremely limited.…”
mentioning
confidence: 99%
“…In critically ill adult patients admitted to the intensive care units during 2007 to 2015, mucormycosis was responsible for 25.8% of fungal infections (5). The mortality rate of infections was extremely high and was reported as 38% to 100% in immunocompromised patients, such as those with hematologic malignancy and hematopoietic stem cell transplantation, and transplant recipients (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%